Предмет: Алгебра,
автор: knasiranasira
B) 3y - (y - 19) = 2y; r) 6x = 1 - (4 - 6x).
Ответы
Автор ответа:
0
B) 3y - (y - 19) = 2y:
Виразимо y:
2y - (y - 19) = 2y
y - 19 = 0
y = 19
R) 6x = 1 - (4 - 6x):
Виразимо x:
6x + 6x = 1 - 4
12x = -3
x = -3/12
x = -1/4
Виразимо y:
2y - (y - 19) = 2y
y - 19 = 0
y = 19
R) 6x = 1 - (4 - 6x):
Виразимо x:
6x + 6x = 1 - 4
12x = -3
x = -3/12
x = -1/4
knasiranasira:
спасибо
Похожие вопросы
Предмет: Литература,
автор: egor2009zolozhckov
Предмет: География,
автор: timonikl2011
Предмет: География,
автор: valentinasnisar72
Предмет: Қазақ тiлi,
автор: grigori94